p53 Deacetylation Alleviates Sepsis-Induced Acute Kidney Injury by Promoting Autophagy - Sun, Maomao; Li, Jiaxin; Mao, Liangfeng; Wu, Jie; Deng, Zhiya; He, Man; An, Sheng; Zeng, Zhenhua; Huang, Qiaobing; Chen, Zhongqing (Frontiers in Immunology, 2021)
Recent studies have shown that autophagy upregulation can attenuate sepsis-induced acute kidney injury (SAKI). The tumor suppressor p53 has emerged as an autophagy regulator in various forms of acute kidney injury (AKI). Our previous studies showed that p53 acetylation exacerbated hemorrhagic shock-induced AKI and lipopolysaccharide (LPS)-induced endothelial barrier dysfunction. However, the role of p53-regulated autophagy in SAKI has not been examined and requires clarification. In this study, we observed the dynamic changes of autophagy in renal tubular epithelial cells (RTECs) and verified the protective effects of autophagy activation on SAKI. We also examined the changes in the protein expression, intracellular distribution (nuclear and cytoplasmic), and acetylation/deacetylation levels of p53 during SAKI following cecal ligation and puncture (CLP) or LPS treatment in mice and in a LPS-challenged human RTEC cell line (HK-2 cells). After sepsis stimulation, the autophagy levels of RTECs increased temporarily, followed by a sharp decrease. Autophagy inhibition was accompanied by an increased renal tubular injury score. By contrast, autophagy agonists could reduce renal tubular damage following sepsis. Surprisingly, the expression of p53 protein in both the renal cortex and HK-2 cells did not significantly change following sepsis stimulation. However, the translocation of p53 from the nucleus to the cytoplasm increased, and the acetylation of p53 was enhanced. In the mechanistic study, we found that the induction of p53 deacetylation, due to either the resveratrol/quercetin -induced activation of the deacetylase Sirtuin 1 (Sirt1) or the mutation of the acetylated lysine site in p53, promoted RTEC autophagy and alleviated SAKI. In addition, we found that acetylated p53 was easier to bind with Beclin1 and accelerated its ubiquitination-mediated degradation. Our study underscores the importance of deacetylated p53-mediated RTEC autophagy in future SAKI treatments.